IITA risk management - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2018)
IITA Risk Management organises risk awareness week on 27-29 June 2016 at IITA Ibadan featuring Risk walk, Photo competition, Debate and Seminars on business continuity planning and risk awareness.